2014
DOI: 10.1021/ic500553v
|View full text |Cite
|
Sign up to set email alerts
|

The First Water-Soluble Hexarhenium Cluster Complexes with a Heterocyclic Ligand Environment: Synthesis, Luminescence, and Biological Properties

Abstract: The hexarhenium cluster complexes with benzotriazolate apical ligands [{Re6(μ3-Q)8}(BTA)6](4-) (Q = S, Se; BTA = benzotriazolate ion) were obtained by the reaction of [{Re6(μ3-Q)8}(OH)6](4-) with molten 1H-BTA (1H-benzotriazole). The clusters were crystallized as potassium salts and characterized by X-ray single-crystal diffraction, elemental analyses, and UV-vis and luminescence spectroscopy. In addition, their cellular uptake and toxicity were evaluated. It was found that both clusters exhibited luminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 37 publications
9
45
0
Order By: Relevance
“…Similar to other [{Re 6 Q i 8 }L a 6 ] complexes based on a {Re 6 Q 8 } 2+ cluster core (Q = S or Se) [10,24,77,78] the powdered samples 1 and 2 emit bright red phosphorescence upon UV photoexcitation (λ ex = 355 nm). Emission spectra are shown in Figure 7.…”
Section: Luminescence Propertiessupporting
confidence: 62%
“…Similar to other [{Re 6 Q i 8 }L a 6 ] complexes based on a {Re 6 Q 8 } 2+ cluster core (Q = S or Se) [10,24,77,78] the powdered samples 1 and 2 emit bright red phosphorescence upon UV photoexcitation (λ ex = 355 nm). Emission spectra are shown in Figure 7.…”
Section: Luminescence Propertiessupporting
confidence: 62%
“…Recently we have shown that the anionic highly hydrophilic cluster complex [33]. Also, cluster complexes [{Re 6 (µ 3 -S) 8 }(BTA) 6 ] 4-and [{Re 6 (µ 3 -Se) 8 }(BTA) 6 ] 4-(BTAbenzotriazolate ion) with pseudo-amphiphilic ligand environment allows the cluster complexes to smoothly penetrate through the cell membrane [34]. In previous report [35] the authors have demonstrated the cellular uptake of [{Re 6 Se 8 }I 6 ] 3-, its subcellular distribution and the mechanisms that may be responsible for its cytotoxic effects.…”
Section: Cell Proliferation/viability and Cellular Uptakementioning
confidence: 99%
“…Furthermore, the anionic hexa-iodo rhenium selenide cluster [Re 6 Se 8 I 6 ] 3− induces 100% early tumor cell death, whereas the same concentration leaves normal cells unaffected, allows for the localization of tumors and enables the observation of tumor regression through fluorescence measurement during treatment. It is therefore concluded that the octahedral rhenium cluster complexes have promising potential for therapeutic and diagnostic applications [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%